2019
DOI: 10.1002/adhm.201801331
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Graphene Coating of Intracortical Probes for Long‐Lasting Neural Activity Monitoring

Abstract: The invasiveness of intracortical interfaces currently used today is responsible for the formation of an intense immunoresponse and inflammatory reaction from neural cells and tissues. This leads to a high concentration of reactive glial cells around the implant site, creating a physical barrier between the neurons and the recording channels. Such a rejection of foreign analog interfaces causes neural signals to fade from recordings which become flooded by background noise after a few weeks. Despite their inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…In addition, there were no significant differences between both implant and non-operated eyes. These findings are consistent with a high biocompatibility of graphenebased electrodes as previously suggested with in vitro studies (Bendali et al, 2013;Convertino et al, 2018), and in vivo studies (Bourrier et al, 2019). However, future works should assess neuronal function to demonstrate further the biocompatibility of the graphene material although this assessment is particularly difficult in blind animals with a flat electroretinogram (Pinilla et al, 2005;Orhan et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, there were no significant differences between both implant and non-operated eyes. These findings are consistent with a high biocompatibility of graphenebased electrodes as previously suggested with in vitro studies (Bendali et al, 2013;Convertino et al, 2018), and in vivo studies (Bourrier et al, 2019). However, future works should assess neuronal function to demonstrate further the biocompatibility of the graphene material although this assessment is particularly difficult in blind animals with a flat electroretinogram (Pinilla et al, 2005;Orhan et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Previous cell culture studies have already demonstrated the high biocompatibility of CVD graphene bounded to a hard material (glass) for retinal neurons (Bendali et al, 2013) as well as investigated its effect on peripheral neurons (Convertino et al, 2018). Additionally, CVD graphene coated onto intracortical probes that were chronically implanted in mice cortex showed that that the presences of graphene had reduced the local density of astrocytes and microglia at the implanted site (Bourrier et al, 2019). Following graphene transfer on soft biocompatible polymer material, the in vivo biocompatibility of graphene in the retina was shown here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, few studies focused on the tissue response to graphene coatings in vivo and the correlative effects on the detection efficiency and time reliability of neural electrodes [ 165 , 166 , 167 ]. The work from Bourrier et al indicated that the proliferations of astrocytes and microglia were significantly reduced around the monolayer graphene-coated probes after 5 weeks of implantation, suggesting that graphene was associated with the reduction of the tissue response due to its flexibility and function as a diffusion barrier [ 168 ]. Moreover, graphene was also able to enhance the neuronal differentiation of human neural stem cells (hNSCs).…”
Section: Carbon Materialsmentioning
confidence: 99%
“…[26] These pioneering experiments paved the road for further implementation of SiNW-FETs at the manufacturing scale, to provide prototypes for various bioapplications, including cancer diagnostics, or detection of DNA, virus, bacteria and biotoxin, explosive gas, protein, nuclei acid for health and security. [27] In comparison with the emerging graphene field effect transistors (G-FETs) that provides several biosuitable properties such as excellent neuronal affinity in vitro [28] and in vivo, [29] high sensitivity, and optical transparency, [30] the silicon technology keeps two main advantages: the spatial resolution [%10 nm vs 10 μm for SiNW-and G-FETs, respectively] and the CMOS compatibility that enables large-scale implementation (at manufacturing level) with a mature technology. Nanoscale sensing has been reported with G-FETs, [31] but controlling sensing sites' location is technologically challenging.…”
mentioning
confidence: 99%